Analysis of central mechanism of cognitive training on cognitive impairment after stroke: Resting-state functional magnetic resonance imaging study. (June 2014) - Lin, Zhi-cheng; Tao, Jing; Gao, Yan-lin; Yin, Da-zhi; Chen, A-zhen; Chen, Li-dian
Objective: To investigate the central mechanism of cognitive training in patients with stroke, using resting state (RS) functional magnetic resonance imaging (fMRI). Methods: Patients with stroke and executive function and memory deficit were randomized to receive computer-assisted cognitive training (treatment group; total 60 h training over 10 weeks) or no training (control group). All participants received neuropsychological assessment and RS fMRI at baseline and 10 weeks. Results: Patients in the treatment group ( n  = 16) showed increased functional connectivity (FC) of the hippocampus with the frontal lobe (right inferior, right middle, left middle, left inferior and left superior frontal gyrus) and left parietal lobe at 10 weeks compared with baseline. Patients in the control group ( n  = 18) showed decreased FC of the left hippocampus–right occipital gyrus, and right hippocampus–right posterior lobe of cerebellum and left superior temporal gyrus. Significant correlations were found between improved neuropsychological scores and increased FC of the hippocampus with the frontal lobe and left parietal lobe in the treatment group only. Conclusions: Increased RS FC of the hippocampus with the frontal and parietal lobes may be an important mechanism of cognitive recovery after stroke.